Taxonomic Features of Seven Serotypes of Simian and Ape Foamy Viruses - Johnston, Paul B. (1971)
Two new simian viruses were recovered from squirrel monkeys and galagos. They possess foamy virus group properties which appear distinct from other virus groups. Serologically they were designated types 4 and 5 and are completely specific from each other and from types 1, 2, 3, 6, and 7 by neutralization tests. The study includes a comparison of the properties of all seven types in one laboratory.